Examining Call for the Dissolution of Indonesian Ulema Council: Siyāsah Syar’íyyah Perspective - Abdul Syatar; Muhammad Imran; M Ilham; Kurniati Kurniati; Marilang Marilang; Kamaluddin Nurdin Marjuni (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
The religious authoritative institution of the Indonesian Ulema Council (MUI), is facing infiltration by members connected with acts of terrorism. This leads to public demands for its dissolution under the banner of